The impact of occupational stress related factors on employees mental health: case of Zim Alloys - Makubaza, Faith (Midlands State University, 2019)
The research sought to explain the impact of occupational stress related factors on employees’ mental health. The research is guided by four research questions which aim to explore the impact of occupational stress related factors, manifestations of mental health problems, coping strategies used by employees and measures that can be taken to minimize the impact of occupational stress related factors. The research was enriched with the transactional theory of stress and the person-environment fit model and relevant literature. A case study was used as a form of research design. Data was collected using the purposive sampling. Semi-structured interviews were administered to the established participants. Data was analyzed using thematic analysis. The study established that employees are subjected to occupational stress related factors such as shift work, retrenchment, long working hours, poor working relations, disciplinary procedures, and accidents. The study established that mental health challenges manifest through loneliness, depression, anxiety, insomnia, alcohol/substance abuse and fatigue. It is the researcher’s findings that adaptive and maladaptive coping strategies namely substance abuse, optimism, resilience, spirituality and avoidance were used. It is the researcher’s findings that there are strategies that can be implemented to minimize the impact of occupational stress which include psychosocial support, effective communication, recreational facilities and effective salary administration.Conclusively, the research discovered challenges experienced by employees and recommendations such as establishment of mental health policies to cater for employees’ mental health needs. The organization should have professionally trained psychologist to help employees with psychological problems.